Slow Dutch Auctions - Carare, Octavian; Rothkopf, Michael (Management Science, 2005)
Theorists have long believed that Dutch auctions are strategically equivalent to standard sealed bidding. However, in recent controlled experiments with actual Dutch and sealed-bid Internet auctions of collectibles, the Dutch auctions produced significantly more revenue. We believe that this happened, in part, because the Internet Dutch auctions are a slow process in which bidders incur incremental transaction costs if they delay bidding. This paper presents models of slow Dutch auctions that include these costs and explain this belief. We first present a decision-theoretic model of a slow Dutch auction. While simple, the decision-theoretic model is fairly general and provides the basic intuition underlying our revenue results. We then develop a game-theoretic model of a slow Dutch auction. We derive two symmetric, payoff-equivalent equilibria of the game in the absence of a cost of return and then consider the more general case of costly return. When the cost of return is in an appropriate range, the seller's expected revenue is an increasing function of that cost.